Change detection on land surface temperature and land use land cover in Jelutong, Jelutong, Perak / Noor Ezlly Shafira Musselihat - Musselihat, Noor Ezlly Shafira (2023)
This study utilized geospatial methodologies and satellite imagery to examine changes in land surface temperature (LST) and land use land cover (LULC) in Jelutong, Perak from 2016 to 2019. The goals cantered on categorizing LULC, deriving LST using Landsat 8, and examining the relationship between LULC and LST. The research aimed to acquire insight into the patterns, trends, and potential effects of these transformations by conducting change detection studies. This study provides valuable inputs for land use planning, development decisions, and the identification of areas at risk of overheating or negative impacts, all while promoting sustainable land use practises. Advanced algorithms were used for LST extraction using Landsat 8 satellite data and Envi software version 5.3, and geospatial techniques were used for land use land cover classification. The study revealed minimal overall changes in land use land cover, with notable changes observed in urban areas and dry areas, while other land cover types demonstrated comparatively stable conditions. Significant changes were detected in developed areas, highlighting the need for sustainable land management practices. In terms of land surface temperature, the year 2019, had higher temperatures than 2016 did, indicating potential variations in urban heat island effects or other regional factors. This study provides valuable insights into the dynamic relationship between LST and land use land cover, highlighting the importance of continuous monitoring and facilitating informed decision-making for sustainable development in Jelutong, Perak and beyond.